2015
DOI: 10.1080/19388160.2015.1077181
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Adoption amongst Chinese Youth during Leisure-based Tourism: Challenges and Opportunities

Abstract: With the spread of Information communications technology (ICT) in China, the tourism industry has come to recognize the importance of examining the factors that influence adoption of smartphones during leisure-based tourism among Chinese 10 youth, a vital segment in what the world's greatest domestic, inbound, and outbound tourism market will be by 2020. Using data collected from undergraduate students at a university in China, this study, based on the technology acceptance model (TAM) and theory of reasoned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Th e Chinese tourists of today -and, above all, tomorrow-are young and affl uent (Skivalou & Filippidi, 2017), independent and adventurous (King & Gardiner, 2015), high-tech and heavy smartphone users (O' Regan & Chang, 2015). Th e Chinese tourist nowadays is very open to the concept of smart tourism and embraces the use of technology while on vacations and takes advantage of new channels of information services.…”
Section: Discussionmentioning
confidence: 99%
“…Th e Chinese tourists of today -and, above all, tomorrow-are young and affl uent (Skivalou & Filippidi, 2017), independent and adventurous (King & Gardiner, 2015), high-tech and heavy smartphone users (O' Regan & Chang, 2015). Th e Chinese tourist nowadays is very open to the concept of smart tourism and embraces the use of technology while on vacations and takes advantage of new channels of information services.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2017) reported that all people regularly use these phones in every activity in their lives. Regan and Chang (2015) defined smart phones as a pocket mobile phone but with stronger capabilities, with large screen, easily internet access and location based support. They offer a lot of features like browsing, downloading, accessing several applications, GPS, camera, video camera, games, video, and audio play back ,…..etc.…”
Section: Smart Phone Technologymentioning
confidence: 99%
“…For measuring performance expectation, items from H.-N. Sung, Jeong, Jeong, and Shin (2015) and Yang and Forney (2013) are adopted. Furthermore, for measuring attitude towards adoption, items from El-Gayar et al (2011), O'Regan andChang (2015), and H.-N. Sung et al (2015). Additionally, items from EscobarRodríguez, Carvajal-Trujillo, and Monge-Lozano (2014) and Kim et al (2013) are used to measure motivation.…”
Section: Methodsmentioning
confidence: 99%
“…Each variable is measured using items taken and adapted from existing literature. Social influence is measured by items from Akbar (2013) and O'Regan and Chang (2015). For measuring performance expectation, items from H.-N. Sung, Jeong, Jeong, and Shin (2015) and Yang and Forney (2013) are adopted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation